(untitled) (The Pakistan Development Review, 1988)
After the 1972 UN conference on "The Human Environment" an increasing number of countries in the developing world initiated environmental policies. This process, however, gained momentum only slowly, as the view was still widely prevailing (and particularly supported by India and Brazil) that environmental protection was a privilege of the industrial countries which developing countries cannot afford. The 1972 conference also brought about a change in the concept of human environment which adapted to the actual conditions and priorities in developing countries by widening the definition and encompassing deforestation, desertification, inadequate water supply, lack of sanitation, poor housing facilities, etc. It was also made clear that in addition to "industrialization-induced" environmental pollution, developing countries suffer particularly from "poverty-induced" environmental hazards. This paper reviews the development of environmental management in Asian developing countries during the Seventies and Eighties and analyses shortcomings of environmental policies in these countries. It also gives an overview of environmental pollution and damages in order to judge the success or failure of environmental policies, and analyses some of the main causative factors of environmental pollution. The paper cannot deal with national characteristics, but has to confine itself to features which are more or less common to most countries and thus focuses on general trends and developments.